Effects of sugar‐free chewing gum sweetened with xylitol or maltitol on the development of gingivitis and plaque: a randomized clinical trial. Issue 4 (21st March 2014) - Keukenmeester, RS; Slot, DE; Rosema, NAM; Van Loveren, C; Van der Weijden, GA
Abstract Objective The objective of this study was to test the effect of sugar‐free chewing gum sweetened with xylitol or maltitol compared to the use of a gum base or no gum on gingivitis and plaque scores under both brushing and non‐brushing circumstances. Methods The design of the study was a four‐group, double‐blinded, randomized controlled study with a 3‐week duration. In each group, the participants did not brush the teeth in the lower jaw designated to develop experimental gingivitis, while maintaining normal oral hygiene procedures in the upper jaw. After professional dental prophylaxis, the participants were allocated into one of four groups (xylitol, maltitol, gum base or no gum). Chewing gum was used five times a day for 10 min. Results 220 participants completed the study and provided evaluable data. The increase in bleeding on marginal probing (BOMP) and plaque scores (PS) in the non‐brushed (lower) jaw with experimental gingivitis was significant in all groups (P < 0.001). As compared to the gum base, the increase in BOMP in the xylitol and maltitol group was significantly lower. In the brushed upper jaw, no significant changes for BOMP were observed from the baseline to the end point of the study, and there were no significant differences in BOMP and PS between the groups. Conclusion In circumstances where regular brushing is performed, no effect of chewing gum was observed on bleeding and plaque scores. In the absence of brushing, chewing xylitol or maltitol gum provided a significant inhibitory effect on gingivitis scores compared to chewing gum base. The difference when compared to the group not using gum was not significant.